2006
DOI: 10.1088/0957-0233/17/7/036
|View full text |Cite
|
Sign up to set email alerts
|

Excess noise measurement in avalanche photodiodes using a transimpedance amplifier front-end

Abstract: We report a versatile system for measuring excess noise and multiplication in avalanche photodiodes, using a transimpedance amplifier front-end and based on phase-sensitive detection, which permits accurate measurement in the presence of a high dark current. The system, which we have used successfully on a wide variety of materials and device structures, can measure reliably the excess noise factor of devices with a capacitance of up to ∼50 pF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 17 publications
1
55
0
Order By: Relevance
“…The system after Li (Lau et al, 2006, Li, 1999) is superior in noise performance to prior reported systems. The transimpedance amplifier provides a signal to noise ratio which is superior to that possible in a 50Ω system.…”
Section: Fig 5 Schematic Diagram Of An Excess Noise Measurement Sysmentioning
confidence: 72%
See 4 more Smart Citations
“…The system after Li (Lau et al, 2006, Li, 1999) is superior in noise performance to prior reported systems. The transimpedance amplifier provides a signal to noise ratio which is superior to that possible in a 50Ω system.…”
Section: Fig 5 Schematic Diagram Of An Excess Noise Measurement Sysmentioning
confidence: 72%
“…The Xie et al (1993) system represents both. Bulman (1983), Ando and Kanbe (1981) and Lau et al (2006) presented systems based on phase sensitive detection. Xie et al (1993) and Toivonen et al (1992) used a DC approach.…”
Section: Measurement Systemsmentioning
confidence: 99%
See 3 more Smart Citations